Combinatorial depletions of G-protein coupled receptor kinases in immune cells identify pleiotropic and cell type-specific functions - Glaser, Katharina M.; Tarrant, Teresa K.; Lämmermann, Tim (Frontiers in Immunology, 2022)
G-protein coupled receptor kinases (GRKs) participate in the regulation of chemokine receptors by mediating receptor desensitization. They can be recruited to agonist-activated G-protein coupled receptors (GPCRs) and phosphorylate their intracellular parts, which eventually blocks signal propagation and often induces receptor internalization. However, there is growing evidence that GRKs can also control cellular functions beyond GPCR regulation. Immune cells commonly express two to four members of the GRK family (GRK2, GRK3, GRK5, GRK6) simultaneously, but we have very limited knowledge about their interplay in primary immune cells. In particular, we are missing comprehensive studies comparing the role of this GRK interplay for (a) multiple GPCRs within one leukocyte type, and (b) one specific GPCR between several immune cell subsets. To address this issue, we generated mouse models of single, combinatorial and complete GRK knockouts in four primary immune cell types (neutrophils, T cells, B cells and dendritic cells) and systematically addressed the functional consequences on GPCR-controlled cell migration and tissue localization. Our study shows that combinatorial depletions of GRKs have pleiotropic and cell-type specific effects in leukocytes, many of which could not be predicted. Neutrophils lacking all four GRK family members show increased chemotactic migration responses to a wide range of GPCR ligands, whereas combinatorial GRK depletions in other immune cell types lead to pro- and anti-migratory responses. Combined depletion of GRK2 and GRK6 in T cells and B cells shows distinct functional outcomes for (a) one GPCR type in different cell types, and (b) different GPCRs in one cell type. These GPCR-type and cell-type specific effects reflect in altered lymphocyte chemotaxis in vitro and localization in vivo. Lastly, we provide evidence that complete GRK deficiency impairs dendritic cell homeostasis, which unexpectedly results from defective dendritic cell differentiation and maturation in vitro and in vivo. Together, our findings demonstrate the complexity of GRK functions in immune cells, which go beyond GPCR desensitization in specific leukocyte types. Furthermore, they highlight the need for studying GRK functions in primary immune cells to address their specific roles in each leukocyte subset.